Implementasi Penilaian Autentik Berbasis Proyek Pada Mata Pelajaran IPS Untuk Mengembangkan Kreativitas Siswa - Faizah Hijriati; Mamat Ruhimat; Dina Siti Logayah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to examine how the implementation of authentic project-based assessment supports the development of students’ creativity in Social Studies learning at the junior high school level. The research method uses a mixed method approach with a descriptive-exploratory design, this study involved 28 seventh grade students at SMP Negeri 29 Bandung as research subjects. Data were collected through observation, interviews, and project assessments using an authentic rubric based on Torrance’s four creativity indicators: fluency, flexibility, originality, and elaboration. The quantitative findings revealed that the students’ average creativity score was 11.8 out of a maximum of 16 (Good category), with originality showing the highest mean (M = 3.14) and flexibility the lowest (M = 2.79). Theoretically, these results reinforce Torrance’s model of creativity and Amabile’s componential theory within the context of social studies. Methodologically, this study introduces an authentic assessment rubric with high reliability (κ = 0.82). The novelty of this research lies in the application of authentic assessment through a three-dimensional physical project involving recycled materials, which integrates students' cognitive, social, and psychomotor aspects. In practice, the findings highlight the importance of designing contextual, sustainability-oriented projects to foster 21st-century competencies